DIMENSI SOSIAL EKONOMI BANTUAN SISWA MISKIN DI TTS NTT - Bello, Francisia W. (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
The BSM cash transfer scheme aimed to reach one-third of Indonesian households  to provide some compensation for the reduction in the fuel subsidy at a time of rapid  fuel and food – particularly rice – price inflation. Cash was disbursed in several rounds in 2007-2014. BSM attracted considerable negative public attention due to widespread protests, chiefly as a result of perceived inaccuracies in relation  to beneficiary selection; some protests were violent, and the programme as a whole suffered from adverse public attention. But BSM is specifically for helping student from elementary school to senior high school